Does Becoming A Volunteer Attenuate Loneliness Among Recently Widowed Older Adults?. (8th July 2017) - Carr, Dawn C; Kail, Ben Lennox; Matz-Costa, Christina; Shavit, Yochai Z
Abstract: Objectives: Loneliness is a significant public health concern, particularly for those who have lost a spouse through widowhood. This study examines whether becoming a volunteer at the time of widowhood is associated with reduction of these risks. Method: A pooled sample of 5, 882 married adults age 51+, drawn from the 2006–2014 waves of the Health and Retirement Study, was used to estimate regression models of the relationship between becoming widowed (relative to staying continuously married) and loneliness, and whether the associated loneliness of having lost a spouse is moderated by starting to volunteer (<2 hr, 2+ hr/week). Results: Our results show that for those who become widowed, loneliness is significantly higher than those who stay continuously married. However, starting to volunteer 2+ hr per week is related to attenuated loneliness among the widowed such that widows who volunteer at that intensity have levels of loneliness similar to those of continuously married individuals volunteering at the same intensity. Discussion: This study suggests higher intensity volunteering may be a particularly important pathway for alleviating loneliness among older adults who have recently become widowed. Results are discussed in light of theory, future research, and potential interventions.